Perancangan Aplikasi Input Laporan Data Single Line Diagram Unit Layanan Pengadaan PLN SUMUT - Indira Febiana; Muhammad Dedi Irawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The State Electricity Company for the North Sumatra Region still uses a manual system, especially in the field of Facilities and Operations (FasOp) in collecting data reports on the Single Line Diagram of Procurement Service Units (SLD-ULP) in North Sumatra. Single Line Diagram (SLD) is a single channel diagram which is currently collected using a manual system so it is not effective and efficient in terms of time and operations, because every employee from each region must collect SLD-ULP data in the form of a manual map and deliver it directly to PLN North Sumatra made through Microsoft Visio. So it is necessary to make SLD-ULP data collection applications to be more effective and efficient. The collection technique used was observation and interviews. After that the authors built an Android-based application using Kodular and Airtable as the database to help employees work more effectively and efficiently.